Ultrasound-assisted extraction of phenolic compounds from mango (Mangifera indica cv. Chok Anan) peel and its inhibitory effect on enzymatic browning of potato puree - Jirasuteeruk, Chotika (Array, 2019)
Enzymatic browning is a serious quality deterioration of fresh-cut fruits and vegetables. Recently, consumers and fruit and vegetable industrial processors have demanded the use of natural antibrowning agents to replace the use of chemicals. Mango (Mangifera indica cv. Chok Anan) peel was prepared in the form of mango peel liquid nitrogen powder. This included extraction by ultrasound or ultrasound combined with stirring. The total phenolic content of mango peel liquid nitrogen powder extract (further in the text: mango peel extract) was the highest after the extraction for 15 min using ultrasound followed by stirring for 15 min. The browning value of potato puree treated with mango peel extract was lower, while its L* value and the hue angle were larger than of samples treated with ascorbic or citric acids during storage for 6 h. Mango peel extract had a competitive inhibitory effect on potato polyphenol oxidase (PPO), which was larger than either ascorbic or citric acid. Its IC50 value was 0.3 mg/mL. Mangiferin, protocatechuic and gallic acid found in mango peel extract had high inhibitory effect on potato PPO, making mango peel a potential natural source of enzymatic browning inhibitor.